Integrating lean management and Islamic civilisation - Mhd. Sarif, Suhaimi; Yahya, Rohaziah (Sejahtera Consumerism Kulliyyah of Economics and Management Sciences IIUM, 2025)
This study examines the integration of Islamic civilizational ethics into the Toyota Management System (TMS), illustrating how spiritual and moral values can enhance contemporary organisational practice. Toyota’s philosophy of Kaizen—continuous improvement—embodies humility, discipline, and collective responsibility, echoing Islamic principles of ihsan (excellence), amanah (trust), and adl (justice). Drawing upon classical scholars such as al-Farabi, Ibn Khaldun, and Ibn Taimiyyah, the paper situates lean management within the broader context of the Tawhidic worldview, where material efficiency is harmonised with moral accountability. Modern thinkers including Ismail al-Faruqi, S.M.N. al-Attas, and M. Kamal Hassan further deepen this perspective by framing productivity as a form of stewardship (khilafah) and moral moderation (wasatiyyah). Through this synthesis, Toyota’s lean philosophy transforms into a model of Sejahtera—a balanced civilisational ethos that integrates operational excellence, social justice, and spiritual consciousness. The study concludes that aligning industrial systems with Islamic values nurtures ethical sustainability, rehumanises capitalism, and realises the Qur’anic vision of responsible governance rooted in divine unity (Tawhid).